Penggunaan Media Quizizz Untuk Mengetahui Peningkatan Pemahaman Materi Siswa Kelas Tinggi Sekolah Dasar - Desi Nursyifa Ramdhani; Syifa Dilla Khansa; Prihantini Prihantini (Politeknik Kampar, 2024)
This study aims to determine the level of material understanding by using QUIZIZZ digital media as a classroom learning evaluation application and improve learning evaluation results. This QUIZIZZ application is also a fun learning application that can build student learning motivation. This research also aims to reveal the weaknesses and advantages of using the QUIZIZZ application. This research uses a qualitative descriptive method, namely literature study (literature study) is often referred to as a series of reading activities, as well as collecting and recording research data by searching for articles, journals, books, and news. The results of the study state that the use of QUIZIZZ digital media can improve the understanding of high-grade students' material because, the use of QUIZIZZ at the time of evaluation increases student motivation because students feel challenged to get the best score. In quizzes, a high sense of competition with friends wants to be the fastest and right, and students feel helped in understanding the material by the use of quiz-based knowledge capital. And also as one of the creativity and innovation that is appropriate and developing in the 21st century.